2018
DOI: 10.1007/s40257-018-0365-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Diagnosis and Management of Photosensitive Disorders

Abstract: Photodermatoses occur in males and females of all races and ages. Onset can be variable in timing and influenced by genetic and environmental factors. Photodermatoses are broadly classified as immunologically mediated, chemical- and drug-induced, photoaggravated, and genetic (defective DNA repair or chromosomal instability) diseases. Advances in the field have led to improved recognition and treatment of many photodermatoses. The purpose of this focused review is to provide an update on the diagnosis and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 230 publications
0
13
0
16
Order By: Relevance
“…This might be as a result of repeated UV exposure reactivating EBV in latent lymphocytes. 14 The emergence of HVLPD is closely associated with ultraviolet light. The malignant transformation of HVLPD has been linked to ultraviolet radiation, and sunlight can both cause and exacerbate skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be as a result of repeated UV exposure reactivating EBV in latent lymphocytes. 14 The emergence of HVLPD is closely associated with ultraviolet light. The malignant transformation of HVLPD has been linked to ultraviolet radiation, and sunlight can both cause and exacerbate skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Previous studies have shown that TCR gene rearrangement is considered a useful tool for distinguishing between classical HV and severe HV. 14 Due to EBV infection, patients may have different levels of EBV DNA in their plasma and Peripheral Blood Mononuclear Cell (PBMC), 15 , 16 and Epstein-Barr virus-encoded RNA (EBER) in situ hybridization of tissues may be positive. In addition, the degree of EBV infection may also be related to the prognosis, but the relevant cases are rarely reported at present.…”
Section: Introductionmentioning
confidence: 99%
“…Since cutaneous lesions of HV patients can be induced by photoprovocation testing, the conceptually accepted hypothesis is that UV radiation with wavelengths between 320 and 390 nm may be the causal agent of HV [8,[25][26][27][28][29]. A single high-dose of UVA irradiation does not induce HV, but repetitive photoprovocation tests at the same site, even with lower doses of UVA irradiation, result in the induction of erythema and vesiculation [29]. However, the mechanism and the chromophore resulting in UV-induced damage in HV are unclear and need further investigation.…”
Section: Uv Irradiation May Induce Hvmentioning
confidence: 99%
“…Monoclonal rearrangement of TRG and/or TRB is regarded as a useful tool for distinguishing classic HV from severe HV [29]. In a large cohort study of HVLPD, 88% of patients carried monoclonal T-cell receptor gene rearrangements [19].…”
Section: Pathological Features and Immunochemical Profilesmentioning
confidence: 99%
“…Since cutaneous lesions of HV patients can be induced by photoprovocation testing, the conceptually accepted hypothesis is that UV radiation with wavelengths between 320 and 390 nm may be the causal agent of HV [8,[25][26][27][28][29]. A single high-dose of UVA irradiation does not induce HV, but repetitive photoprovocation tests at the same site, even with lower doses of UVA irradiation, result in the induction of erythema and vesiculation [29]. However, the mechanism and the chromophore resulting in UV-induced damage in HV are unclear and need further investigation.…”
Section: Uv Irradiation May Induce Hvmentioning
confidence: 99%